PELAKSANAAN EKSEKUSI DALAM SENGKETA WARIS TANAH PUSAKO TINGGI (STUDI PADA SUKU PAGAR CANCANG DI JORONG KURANJI NAGARI GUGUAK VIII KOTO KECAMATAN GUGUK KABUPATEN LIMA PULUH KOTA) - Febrianti. Z, Cindy; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
West Sumatera is one of the provinces in indonesia which is still very thick with its costums. As an area that still really respect the customs of West Sumatera when talking about land issues using Minangkabau Customary Law. But when the land issue can’t be resolved under the Minangkabau Adat Law, it can continue to the court stage. If the court has decided a decision that has permanent legal force, a decision of the judge will be carried out which is called execution. In this case, it is related to the issue of executing the inheritance of high pusako lands in the Cancangfence tribe which occurred in Jorong Kuranji, Nagari Guguak VIII Koto, Kecamatan Guguk, Kabupaten Lima Puluh Kota. The purpose of writing this thesis is, first, to find out the execution of the high pusako land inheritance dispute in the Cancang fence tribe in Jorong Kuranji, Nagari Guguak VIII Koto, Kecamatan Guguk, Kabupaten Lima Puluh Kota, second, to find out the settlement of the execution of the high pusako land inheritance dispute in the Cancang fence tribe.in Jorong Kuranji, Nagari Guguak VIII Koto, Kecamatan Guguk, Kabupaten Lima Puluh Kota.From the results of the research on the problem, there are several things that can be concluded, first, the ownership of high pusako land is based on the court decision that the defendant must leave the high pusako land controlled by the plaintiff. Second, the settlement of the execution of inheritance disputes that occurred in Jorong Kuranji, Nagari Guguak VIII Koto, Kecamatan Guguk, Kabupaten Lima Puluh Kota, namely this settlement initially used the method of settlement through ninik mamak to Kerapatan Adat Nagari but did not find common ground, after that it was resolved by the court from District Court, High Court, to the Supreme Court.Keywords: Custom, Land and Execution